Respiratory health of brickworkers in Cape Town, South Africa. Background, aims and dust exposure determinations. - Myers, JE; Lewis, P; Hofmeyr, W (Scandinavian Journal of Work, Environment & Health, 1989)
The respiratory health and work environment of 575 brickworkers in five brickworks in Cape Town, South Africa, were investigated by means of a questionnaire, a physical examination, pulmonary function testing, chest radiography, and dust measurements. This study presents the background, aims, and methods of the determining dust exposure assignments. The mean concentrations of respirable dust and total dust were 2.22 and 15.16 mg/m3, respectively, with a mean free-silica percentage of 2.1%. Subjective and objective, as well as categorical and continuous, dust indicators were constructed for subsequent analyses, together with findings from the health survey, which are reported elsewhere.